Agro-morphological characterization of tarwi (Lupinus mutabilis Sweet) accessions using descriptors and spectral metrics derived from UAVs - Peña-Elme, Eunice (2025)
Tarwi (Lupinus mutabilis S.) is a legume native to the Andes, recognized for its high nutritional value, which gives it great potential in food security programs. Therefore, understanding and advancing the conservation of its morphological diversity is essential. In this study, 140 accessions from the national germplasm collection of the National Institute of Agrarian Innovation of Peru were evaluated, along with two cultivars ("INIA 445 Masacanchino" and "Andenes 90"). A traditional agro-morphological characterization was conducted using 16 quantitative and 40 qualitative descriptors, complemented by phenological data obtained from time series of reflectance indices generated by Unmanned Aerial Vehicles (UAVs). Additionally, a principal component analysis (PCA) was applied to select the most relevant variables, and a clustering analysis along with a dendrogram was developed to classify the accessions. The results revealed significant differences between groups (p < 0.05) in terms of inflorescence length, number of pods on the main axis, number of primary branches, and yield per plant. Likewise, the morphological groups exhibited variations in phenophases derived from the Normalized Difference Vegetation Index (NDVI). Four morphological groups were identified: group 3 (G3) showed the highest growth rate followed by a decline, while group 4 (G4) stood out for its highest initial growth rate. Furthermore, the observed homogeneous phenological conditions indicated that groups 1 (G1) and 4 (G4) matured earlier, making them promising candidates for selection. These findings demonstrate the wide genetic variability of tarwi, which can be exploited in breeding programs for the development of new cultivars. Thus, the study highlights the importance of morphological characterization in understanding the variability of an understudied crop such as tarwi, contributing to conservation and promoting its protection and sustainability.